Mapping urban expansion and its effect on the surrounding land uses using GIS and remote sensing. A case study in Debre Tabor Town, Ethiopia - Solomon Eniyew (Journal of Degraded and Mining Lands Management, 2018)
In recent years, GIS and Remote Sensing technology has played a vital role in studying urban growth and development. This study is aimed to assess the effects of urban expansion on the surrounding land uses using GIS and Remote Sensing in Debre Tabor Town. Remote sensing data or products such as Aerial photograph (1984), Quick Bird Satellite Image (2000), and Aerial photograph (2016) were used to compute spatial or temporal changes of land use land cover due to urban expansion. ERDAS Imagine and Arc GIS software were used to analyze, model and map the data. The study revealed a significant change in urban boundary and urban land-use land cover between 1984 and 2016. The urban boundary expansion rate between the years 1984 and 2000 was 69.06%, higher than the rate experienced thereafter to the year 2016 (18.86%). However, for the last thirty-two years, between 1984 and 2016, the overall boundary increasement of almost eighty one percent (81.4) was very magnificent. The study also indicated that the area experiencing rapid increase in built-up areas (80.93 %), and agricultural land (23.81%). However, sharp decrease of forest by 36.07%, and open land by 65.02% was seen in the same periods of years. Built-up area expansion was found to have increased by expanding the urban boundary at the expense of open land, agricultural land, and forests. Therefore, integrating GIS and remote sensing technology for urban expansion mapping is a worthy method. Hence, it is recommended that it will be cost effective if the results of this study will be incorporated into ongoing urban planning and land use by concerned bodies.